2016
DOI: 10.1002/2016rs006134
|View full text |Cite
|
Sign up to set email alerts
|

On the consistency of the SuperDARN radar velocity and E × B plasma drift

Abstract: Joint observations of the Rankin Inlet (RKN) and Inuvik Super Dual Auroral Radar Network (SuperDARN) HF radars and Resolute Bay incoherent scatter radar (RISR) are used to assess consistency in their plasma flow velocity measurements. The analysis covers more than 500 h of successful concurrent measurements. We demonstrate that, overall, the radars show close velocities, although there were minor differences including SuperDARN velocity underestimation, in line with previous publications, and the persistent oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 29 publications
6
23
0
Order By: Relevance
“…We note the median, average, and standard deviation of the distribution in each panel. We note that Gillies et al (2009) demonstrated that the SuperDARN flow velocities are underestimated when compared with DMSP flow velocities by~1.2 times, and Koustov et al (2016) found that the SuperDARN velocities are underestimated when compared with Resolute Bay incoherent scatter radar (RISR) by~1.3 times. The underestimation occurs because the refractive index in the scattering region is not taken into account, and therefore, the inferred ionospheric velocities may be underestimated.…”
Section: Mesoscale Flow Velocitymentioning
confidence: 81%
See 1 more Smart Citation
“…We note the median, average, and standard deviation of the distribution in each panel. We note that Gillies et al (2009) demonstrated that the SuperDARN flow velocities are underestimated when compared with DMSP flow velocities by~1.2 times, and Koustov et al (2016) found that the SuperDARN velocities are underestimated when compared with Resolute Bay incoherent scatter radar (RISR) by~1.3 times. The underestimation occurs because the refractive index in the scattering region is not taken into account, and therefore, the inferred ionospheric velocities may be underestimated.…”
Section: Mesoscale Flow Velocitymentioning
confidence: 81%
“…The underestimation occurs because the refractive index in the scattering region is not taken into account, and therefore, the inferred ionospheric velocities may be underestimated. As data users we did not apply this factor to our results, especially since Koustov et al (2016) demonstrated that~37% of the LOS velocity data are overestimated when index of refraction corrections are implemented. Figure 4 shows the velocity PDFs of equatorward flows observed in the polar cap (top row) and the auroral oval, the latter separated by the higher latitude station (RANK: middle row) and the lower latitude station (SAS: bottom row).…”
Section: Mesoscale Flow Velocitymentioning
confidence: 99%
“…The DMSP study by Drayton et al (2005) compared only~750 velocities. More recent studies by Koustov et al (2009), Bahcivan et al (2013), and Koustov et al (2016) used more data points (on the order of 2000-3000), but still fewer than the number used in this study. The reasons this study had much more velocity data than past studies are that the time under consideration is longer compared to other studies and the spatial overlap of the two radars is significant (no previous study considered 35 SuperDARN range gates).…”
Section: Overallmentioning
confidence: 97%
“…However, this explanation cannot 35 account for large differences of more than 20-30%. Koustov et al (2016) stressed the original finding by Xu et al (2001) that the HF velocity magnitudes substantially smaller (up to a factor of 2) than the E×B drift component for high-speed flows of >1000 m/s. Furthermore, often the HF velocity magnitudes are above the E×B component (e.g.…”
Section: Introductionmentioning
confidence: 75%
“…Furthermore, often the HF velocity magnitudes are above the E×B component (e.g. Ruohoniemi et al, 1987;Koustov et al, 2016;Gillies et al, 2018). Such observations have been interpreted in terms of lateral deviation of 40 HF radar beams (Koustov et al, 2016;Gillies et al, 2018).…”
Section: Introductionmentioning
confidence: 99%